PELAKSANAAN SUPERVISI AKADEMIK UNTUK MENINGKATKAN KETRAMPILAN GURU DALAM MENERAPAKAN METODE SAINTIFIK DI SDN 5 SELATPANJANG TAHUN 2017 - Budiherti Budiherti (Universitas Negeri Medan, 2020)
Abstract: Implementation of Academic Supervision to Improve Teacher Skills in Applying Scientific Methods at Selat Panjang 5 2017 Elementary School. The overall results of this study prove that academic supervision can improve the ability of elementary school teachers to apply scientific methods. This is evidenced by the results of the first cycle research, namely the results of the score obtained by SDN 5 Selat Panjang teachers were 11 with a maximum score of 15 and an expectation score of 11, so the ability of SDN 5 Selat Panjang teachers in applying the scientific method was quite good. In cycle II, the score increased. The results of the scores obtained by SDN 5 Selatpanjang teachers in cycle 2 increased to 14 with a maximum score of 15 and an expectation score of 11, so the ability of SDN 5 Selatpanjang teachers in applying the scientific method was classified as good. Keywords: Academic Supervision, Teacher Skills in Applying Scientific Methods Abstrak: Pelaksanaan Supervisi Akademik Untuk Meningkatkan Ketrampilan Guru Dalam Menerapakan Metode Saintifik Di Sdn 5 Selatpanjang Tahun 2017. Hasil keseluruhan penelitian ini membuktikan bahawa Supervisi akademik dapat meningkatkan kemampuan guru SD dalam menerapkan metode saintifik. Hal ini di buktikan dengan hasil penelitian siklus I yakni hasil skor yang di dapatkan Guru-guru SDN 5 Selat panjang adalah 11 dengan skor maksimal 15 dan skor harapan 11 maka kemampuan Guru-guru SDN 5 Selat panjang dalam menerapkan metode saintifik sudah tergolong baik. Pada siklus II, hasil skor meningkat. Adapun hasil skor yang di dapatkan Guru-guru SDN 5 Selatpanjang pada siklus 2 meningkat menjadi 14 dengan skor maksimal 15 dan skor harapan 11 maka kemampuan Guru-guru SDN 5 Selatpanjang dalam menerapkan metode saintifik sudah tergolong baik. Kata Kunci:Supervisi Akademik , Ketrampilan Guru Dalam Menerapakan Metode Saintifik